1998
DOI: 10.1111/j.1532-950x.1998.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Kinetics of Carprofen, Administered Preoperatively or Postoperatively, for the Prevention of Pain in Dogs Undergoing Ovariohysterectomy

Abstract: Carprofen provides effective analgesia after canine ovariohysterectomy. The timing of analgesic administration is important to optimize the control of postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(201 citation statements)
references
References 38 publications
(2 reference statements)
5
185
1
3
Order By: Relevance
“…Arterial blood pressure should be monitored and maintained within a normal range during anesthesia when carprofen or meloxicam are administered with butorphanol as premedication for dogs. Both clinical doses of carprofen and meloxicam provide effective postoperative analgesia when preoperatively administered [17][18][19], although meloxicam has higher in vitro selectivity of COX-2 inhibition than carprofen in dogs [5,15]. We also did not find any difference in sevofluranesparing effect between the treatments with carprofen alone and meloxicam alone, and between carprofen with butorphanol and meloxicam with butorphanol in dogs.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Arterial blood pressure should be monitored and maintained within a normal range during anesthesia when carprofen or meloxicam are administered with butorphanol as premedication for dogs. Both clinical doses of carprofen and meloxicam provide effective postoperative analgesia when preoperatively administered [17][18][19], although meloxicam has higher in vitro selectivity of COX-2 inhibition than carprofen in dogs [5,15]. We also did not find any difference in sevofluranesparing effect between the treatments with carprofen alone and meloxicam alone, and between carprofen with butorphanol and meloxicam with butorphanol in dogs.…”
Section: Discussionmentioning
confidence: 47%
“…Carprofen and meloxicam are COX-2 selective inhibitors that have been shown to produce analgesic effects with minimal side effect in dogs [5,6,15,34]. Their preoperative administration to dogs undergoing ovariohysterectomy has been reported to produce a greater analgesic effect in the early postoperative period than does postoperative administration [18,19]. Also carprofen and meloxicam have been reported to relieve signs of pain for up to 24 hr in dogs undergoing orthopaedic surgery [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative administration in dogs is superior in efficacy to postoperative use, consistent with results of multiple studies performed in humans. 32 Similar studies have not been conducted in cats undergoing anesthesia, but one feline study revealed no alteration in glomerular filtration rate measured by iohexol clearance after 5 days of oral meloxicam. 27 if iV access is not possible and normotension cannot be achieved with certainty, the Task Force recommends limiting the use of NSAiDs to postsurgical administration.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 97%
“…These simple scales are subjective, and are only widely used because of their simplicity 33 . A number of composite pain assessment scales have been developed from the three basic ones mentioned above, for example, the 'dynamic' and 'interactive' visual assessment scale (DIVAS) used in a study of the analgesic efficacy of carprofen in dogs 21 and the validated Glasgow Composite Pain Tool 14 . A composite scale modified from the University of Melbourne Pain Scale and the Glasgow Composite Pain Tool was used for assessment of pain in this study.…”
Section: Introductionmentioning
confidence: 99%